Phase 3 Trial to Compare Postoperative Chemotherapy with Observation in Stage I or II Endometrial Cancer - Vinall, Maria (MD Conference Express, 2014)
Patients with stage I or II endometrial cancer are generally treated with surgery. Despite radical surgery, however, patients with medium- or high-risk stage I and II endometrial cancers are still at significant risk of local and distant progression. A current phase 3 study [NCT01244789] is preparing to evaluate whether survival can be improved in intermediate- and high-risk early-stage patients by offering postoperative chemotherapy instead of postoperative observation alone (standard strategy), as discussed in this article.